CHARACTERIZATION AND EVALUATION OF ORYZA NIVARA AND ORYZA RUFIPOGON - S. K. CHOUHAN,; A. K. SINGH,; S. APARAJITA,; M. RAM,; P. K. SINGH,; N. K. SINGH, (The Bioscan, 2014)
Field experiment was conducted during wet season 2009-10 at Agricultural Research Farm, Banaras Hindu University, Varanasi Uttar Pradesh to evaluate and characterize thirty five wild rice accessions for fourteen quantitative and twelve qualitative traits. Analysis of variance revealed sufficient variability for all the quantitative traits. The magnitude of phenotypic coefficient of variation was higher to corresponding genotypic coefficient of variation. High heritability coupled with high genetic advance as per cent of mean was found in the trait fertile spikelet per panicle, total number of grains per panicle and grain yield per plant. The qualitative traits variation were found to be high for leaf blade colour, flag leaf angle, panicle exertion, stigma colour and apiculus colour; basal leaf sheath colour, leaf blade pubescence, panicle type, sterile lemma, awning and threshability showed moderate whereas low variability was recorded in leaf senescence. The accessions NKSWR-48, NKSWR-64 and NKSWR-75 are found to be most promising for panicle length, fertile spikelet per panicle, spikelet fertility percentage, test weight and grain yield per plant. The result suggested that these accessions are valuable resource and can be utilized for yield and yield traits.